Concepções de professores sobre a participação da família na Educação Infantil - Nascimento, Renata Cardinali do (2023)
The general objective of this research was to analyze, through the eyes of the teachers, the possible participatory actions of families in Early Childhood Education. The research problem arose from the professional experience of the researcher. The theoretical framework used was based on post-critical theories, as main authors Edgar Morin, Phillip Ariès, Vera Iaconelli, Telma Vinha and Miguel Arroyo; Paulo Freire, Sueli Bravi Conte, Ezequiel Silva, Marli André; Menga Ludke; Marli André, Wendy Olsen and Mirian Goldenberg. The methodology chosen for this research work was a qualitative approach and proposed to analyze the school-family relationship from the point of view of Early Childhood Education teachers at a particular private school in the municipality of Cotia, in the city of São Paulo. The research subjects were four kindergarten teachers who had different periods of experience in the area and interest in discussing themes related to the school and family context. The instruments for data collection were document analysis and a questionnaire related to the meaning attributed to the role of the family in the development of children, the conceptions of teachers about the role of the family in Early Childhood Education and the teaching actions related to the participation of families in school. The document analysis resulted in a repertoire for deepening studies on the school-family relationship, dialogue, and clarity of individual and collective intentions - inside and outside the school - to involve the student and the school community, as actions that need to exist and be shared at school meetings so that integration remains strong and exchanges enriching. For the analysis of the collected data, the six categories were used: conceptions about the parents' participation in the children's development; conceptions about the role of the family in Early Childhood Education; family responsibilities in school routine; teacher responsibilities; the challenges of the relationship between school and family and fundamental aspects for family participation to occur. The main results of the research indicated the importance of knowledge and legitimization of rights of children by their educators and family members, the importance of public policies aimed at early childhood, the school as a space for dialogue for social changes, the family as being powerful pillar of support for the child and revealed that the teachers consider important the constant participation of the family in the school routine. The formative proposal, presented from the result of the data analysis, had the purpose of structuring, through stages, actions that could promote closer ties between family and school for the integral development of the child in the context of Early Childhood Education